2021
DOI: 10.1371/journal.pcbi.1009291
|View full text |Cite
|
Sign up to set email alerts
|

Review of machine learning methods for RNA secondary structure prediction

Abstract: Secondary structure plays an important role in determining the function of noncoding RNAs. Hence, identifying RNA secondary structures is of great value to research. Computational prediction is a mainstream approach for predicting RNA secondary structure. Unfortunately, even though new methods have been proposed over the past 40 years, the performance of computational prediction methods has stagnated in the last decade. Recently, with the increasing availability of RNA structure data, new methods based on mach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 135 publications
0
50
0
Order By: Relevance
“…Similarly, a powerful LNP degradation model, embracing thermodynamic stability, aggregation, and physical degradation, could predict both in-process and in vivo stability. Following the same logic, the available RNA sequence design strategy, underpinned by various data-driven, hybrid, and molecular dynamic modeling tools, could consider the sequence manufacturability in addition to RNA stability and translation [41,[115][116][117]. The secondary structure is indeed known to impact in-process degradation and capping accessibility and could play a potential role in LNP formation [37].…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Similarly, a powerful LNP degradation model, embracing thermodynamic stability, aggregation, and physical degradation, could predict both in-process and in vivo stability. Following the same logic, the available RNA sequence design strategy, underpinned by various data-driven, hybrid, and molecular dynamic modeling tools, could consider the sequence manufacturability in addition to RNA stability and translation [41,[115][116][117]. The secondary structure is indeed known to impact in-process degradation and capping accessibility and could play a potential role in LNP formation [37].…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Examples are mfold [ 18 ], the first MFE-based RNA secondary structure prediction tool, the Vienna RNA package [ 19 ], UNAfold [ 20 ] and RNAstructure [ 21 ]. Recent advances in deep learning allow end-to-end prediction of RNA base-pairing structures with improved performance not only in canonical base pairs but also in pseudoknots and non-canonical base pairs associated with tertiary interactions [ 22–25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we will provide an overview of recent progresses in experimental and computational approaches to RNA SASA as it has been an overlooked area of research. Other recent reviews on studies of RNA secondary or tertiary structures can be found elsewhere [ 14 , 22 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, there have been major interests in determining and understanding RNA secondary structures, via both experiment and computation (10)(11)(12). In recent years, with the emergence of sizeable RNA structure databases and the accessibility of powerful machine learning algorithms, data-centric deep-learning-based models, the subject of this study, have been successfully developed for RNA secondary structure prediction (13).…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of efficient algorithms, especially based on dynamic programming and related techniques (17), have also been introduced along with improved scoring parameters (15,16). However, traditional algorithms have struggled to make significant gains in performance in the recent decade (13).…”
Section: Introductionmentioning
confidence: 99%